Effect Of Work Environment And Motivation On Employee Performance With Job Satisfaction As A Mediation - Kurniawanto, Hari; Rahmadi, Zara Tania; Wahyudi, Muhammad Aria (IJOSMAS, 2022)
This study aims to examine the effect of work environment and motivation on job satisfaction and its impact on performance, in this study will examine job satisfaction as a mediating variable. Data were collected from 100 respondents, namely employees at modern minimarkets in Jakarta by purposive sampling method, with the criteria of employees who have worked for more than 1 year and want to fill out a questionnaire. The collected data was tested by path analysis method using AMOS 24.00. The results of this study are the work environment has a significant effect on job satisfaction, motivation has a significant effect on job satisfaction, the work environment has a significant effect on performance, motivation has a significant effect on performance, and job satisfaction is a significant mediating variable for work environment variables and motivation on performance.